POTENSI LIMBAH LIGNOSELULOSA KELAPA SAWIT DI KALIMANTAN SELATAN UNTUK PRODUKSI BIOETANOL DAN XYLITOL - Asma Nadia; Asma Fauziah; Ersha Mayori; Sunardi Sunardi (Universitas Lambung Mangkurat, 2017)
Abstract. The oil palm is type of plantation sector with the largest commodity being developed by state-owned, private-companies, and also smallholders in South Kalimantan. The total area and production of oil palm in 2017 in South Kalimantan are 455.674 ha and 1.3 million ton, respectively. Oil palm wastes such as empty fruit bunch and oil palm frond are residue from palm oil industry can be utilized as cellulose and hemicellulose feedstock which can be converted into second-generation bioethanol as fuel substitute and xylitol as low caloric sweetener for sugarcane substitute. This article to discuss the potential, process, and opportunity for utilization of lignocellulosic waste of oil palm in South Kalimantan as raw material for bioethanol and xylitol.Keywords: lignocellulose, oil palm, bioethanol, xylitol